THE EFFECTIVENESS OF PICTURE SERIES MEDIA FOR IMPROVING NARRATIVE WRITING SKILLS IN JUNIOR HIGH SCHOOL - Fitriani Fitriani; Akmaluddin Akmaluddin (SENSEI RESEARCH CENTER, 2024)
Writing is a difficult skill for many junior high school students, especially narrative writing. Students often do not know what to write and their story is not well organized. Picture series media can be used to help students in writing narrative texts. This study discusses the effectiveness of picture series media in improving students' narrative writing skills. The study used a mixed-method design with an experimental class and a control class. The data were collected through a writing test, observation, interview, and journal. The result shows that the experimental class was better than the control class and that students gave a positive response to the use of picture series. Therefore, picture series media can be used by teachers in teaching narrative writing.